Urban environment and climate condition-related phenotypic plasticity of the common wasp Vespula vulgaris - Badejo O; Leskinen JTT; Koistinen A; Sorvari J (ALMA MATER STUDIORUM, UNIV BOLOGNA, 2022)
Environmental alteration for urban development prompts ecological changes across urban centres, ranging out towards the surrounding undisturbed areas. These impact on organisms living across the urban-rural gradient and insects, being widely distributed in nature, are confronted with adaptive choices in such situations. The temperature in urban cores is generally higher due to the urban heat island effect. Thus, insects might modify their behaviour or morphology to cope with the urban environment. The common wasp Vespula vulgaris (L.) has shown adaptive capability as its colour pattern varies between years and geographic distribution. Our study assessed the impact of the built urban environment and summers of differing weather conditions on the common wasp by studying the melanic pigmentation on the abdomen. Samples were collected from urban zones in three cities and their adjacent rural zones in Finland. In one location samples were also collected from two different summers to see if climate condition difference between years can drive morph variation in the 1st and 2nd tergite. We also studied the structure of the cuticle and discovered a structure similar to xanthopterin granules embedded in the yellow stripes of the cuticle, this pigment acts as solar cells and is useful in thermoregulation. Our results showed that the common wasps had differences in the frequency of colour morphs of 2nd tergite between years with different weather and between urban and rural zones in the largest city, Helsinki. Wasps from urban and rural zones showed similar trend for the proportion of black and yellow pigmentation. Common wasps seem to have capability to adapt their pigmentation to correspond with prevailing summer and urban climate conditions, thus reaching better balance between heating and energy storing components in their cuticle.